Peranan Efikasi Diri Guru Dalam Prestasi Belajar Siswa - Anisah Anisah; Ferdian Arie Bowo; eka wahyu hidayat (Manajerial, 2021)
Education is one of the most important factors to create a quality generation in the future. The main problem that becomes the focus of the problem related to the quality of learning that is interesting to study in an effort to improve student achievement is teacher self-efficacy. The meth[1]od used in this study is a qualitative method with a descriptive approach. The data of this research are primary data and secondary data collected through interviews and observations. The results of the study indicate that the teacher in addition to acting as a teacher, educator and mentor, through teacher self-efficacy can increase student learning achievement to the maximum so that students are able to obtain maximum learning outcomes in accordance with the educational goals that have been set